Community readiness for childhood obesity prevention programs: findings from an urban population in Iran. (28th October 2020) - Niknam, Mahdieh; Omidvar, Nasrin; Amiri, Parisa; Eini-Zinab, Hassan; Kalantari, Naser
Summary: This study aimed to examine the Iranian local communities' readiness stage to engage with childhood obesity prevention programs for late primary school children in districts 2 and 16 of Tehran as the representatives of high and low socio-economic districts, respectively. First, a Delphi approach was conducted to assess the socio-cultural necessity/appropriateness and adequacy of the community readiness model and its dimensions as a planning basis for childhood obesity prevention program(s) in Iran. Then, the community readiness interview guide's translation, modification, content and face validity were performed. Finally, 66 interviews with key informants were conducted and scored to assess community readiness. The socio-cultural necessity/appropriateness and adequacy of community readiness model and its dimensions were confirmed by Delphi participants and two questions were added to the interview guide. Content and face validity of the interview guide were at acceptable levels. Assessment of the community readiness based on the key informants' perspective showed that the overall mean readiness score of targeted local communities was 4.61 ± 0.54 and 4.22 ± 0.26 in high and low socio-economic districts, respectively, corresponded to 'preplanning stage'. The highest score was 5.00 ± 0.48 correspond to the 'preparation stage', which belonged to girls' schools in district 2. Small differences were found in the readiness stage of local communities by sex and socio-economic status of schools. The results highlight the need to increase community awareness, gain their support to recognize childhood obesity as a priority, address cultural misconceptions and improve the obesity prevention programs to achieve a higher level of readiness.